(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
The article examines religious axiological units in Uzbek and English as significant linguistic and cultural phenomena. Axiological units—lexical, phraseological, and discursive elements that encode values—are analyzed as carriers of religious worldviews, moral norms, and evaluative meanings. Drawing on axiological linguistics, pragmatics, and discourse analysis, the study compares how Islamic and Christian traditions shape value-laden language in Uzbek and English respectively. The analysis identifies dominant axiological categories such as faith, morality, humility, sin, righteousness, and reward, explores their linguistic realization, and discusses implications for translation and intercultural communication.